The house of my mother : a daughter's quest for freedom - Franke, Shari (Gallery Books, 2025)
"Shari Franke's childhood was a constant battle for survival. Her mother, Ruby Franke, enforced a severe moral code while maintaining a façade of a picture-perfect family for their wildly popular YouTube channel 8 Passengers, which documented the day-to-day life of raising six children for a staggering 2.5 million subscribers. But a darker truth lurked beneath the surface--Ruby's wholesome online persona masked a more tyrannical parenting style than anyone could have imagined. As the family's YouTube notoriety grew, so too did Ruby's delusions of righteousness. Fueled by the sadistic influence of relationship coach Jodi Hildebrandt, together they implemented an inhumane and merciless disciplinary regime. Ruby and Jodi were arrested in Utah in 2023 on multiple charges of aggravated child abuse. On that fateful day, Shari shared a photo online of a police car outside their home. Her caption had one word: "Finally." For the first time, Shari will reveal the disturbing truth behind 8 Passengers and her family's devastating involvement with Jodi Hildebrandt's cultish life coaching program, "ConneXions." No stone is left unturned as Shari exposes the perils of influencer culture and shares for the first time her battle for truth and survival in the face of her mother's cruelty."--